Horticultural Therapy - Eva C. Worden; Theodora M. Frohne; Jessica Sullivan (EDIS)
Horticulture is the art and science of growing plants. Horticultural therapy is the practice of engaging people in horticultural activities to improve their bodies, minds, and spirits. Therapeutic benefits occur when people are exposed to plants, and when they take part in planning, planting, growing, and caring for plants. Horticultural therapy is an adaptable tool for clients of all ages and abilities. This document is ENH970, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date January 21, 2004.